UJI VALIDITAS PENGEMBANGAN TES UNTUK MENGUKUR KEMAMPUAN PEMAHAMAN RELASIONAL PADA MATERI PERSAMAAN KUADRAT SISWA KELAS VIII SMP - Riyani, Rizki; Maizora, Syafdi; Hanifah, Hanifah (JP2MS, 2017)
The purpose of this study is to know the validity of test development to measure relational understanding. This study is motivated by the test questions that are usually given by the teacher does not contain procedural calculations and have not varied yet. Type of this study is Reseach and Development by adopting 4-D development procedures. The instruments of this study were validation sheets. Validation was done by two lecturers of the Faculty of Teacher Training and Education, University of Bengkulu, and a teacher of class VIII SMP Negeri 01 Kabupaten Kepahiang. The result shows that developing test is categorized as  valid as well as test can be used.Keywords: Measure Relational Understanding, Research and Development, Quadratic Equation